Label-free tracking and mass measurement of single protein complexes on lipid bilayers - Foley, EDB (2022)
Protein-protein interactions are essential for biological processes, but can display a level of polydispersity that is difficult to study with bulk measurements. Recently, mass photometry, a label-free single molecule imaging technique, has been used to quantify protein-protein interactions by measuring the mass of single proteins. So far, however, measurements are limited to solution-based systems and nM concentrations. Here, we aim to expand the applications of mass photometry to proteins on lipid bilayers, and to increase the concentration range of solution-based measurements.